'The Harmony of One Choir'? Music and Social Unity in Reformation Heidelberg. Issue 1 (29th July 2020) - Laube, Matthew
Abstract: From early in the Reformation, Protestant leaders viewed music as a powerful tool not only for educating their followers, but also for forging unity within diverse and dispersed communities. Such a belief found expression in official and unofficial religious contexts, and left its mark on printed devotional material, congregational hymn books, public policies of church authorities, and the musical activities of individual churches. At the same time, the manner in which a person accessed, experienced and produced music in a Reformation urban environment was conditioned as much by social factors such as age, gender, social station and personal contacts, as by confessional affiliation and policy. Using a corpus of previously unexploited sources from the Protestant city of Heidelberg, this article challenges the rhetorical and outdated binary notions of social 'harmony' and 'discord'. It argues that music in a Reformation city — whether congregational song in churches, secular song in taverns, inns and streets, or domestic devotional song — could function as a powerful platform for emphasizing rather than dissolving a range of meaningful social differences, even as it created new kinds of unity across urban society.